Induced pluripotent stem cells from domesticated ruminants and their potential for enhancing livestock production - Weeratunga, Prasanna; Harman, Rebecca M.; Van de Walle, Gerlinde R. (Frontiers in Veterinary Science, 2023)
Ruminant livestock, including cattle, sheep, goat, and buffalo, are essential for global food security and serve valuable roles in sustainable agricultural systems. With the limited availability of embryonic stem cells (ESCs) from these species, ruminant induced pluripotent stem cells (iPSCs) and iPSC-like cells provide a valuable research tool for agricultural, veterinary, biomedical, and pharmaceutical applications, as well as for the prospect of translation to human medicine. iPSCs are generated by reprogramming of adult or fetal cells to an ESC-like state by ectopic expression of defined transcription factors. Despite the slow pace the field has evolved in livestock species compared to mice and humans, significant progress has been made over the past 15 years in using different cell sources and reprogramming protocols to generate iPSCs/iPSC-like cells from ruminants. This mini review summarizes the current literature related to the derivation of iPSCs/iPSC-like cells from domesticated ruminants with a focus on reprogramming protocols, characterization, associated limitations, and potential applications in ruminant basic science research and production.